LANGUAGE TRAINING IMPROVEMENT OF FUTURE ENGLISH TEACHERS BY MEANS OF INNOVATIVE TECHNOLOGIES - Арістова, Н. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In the article it is discovered the necessity of the use of innovative technology "ELP" in English language teaching in the educational process of nonlinguistic modern schools with a view to further improvement